Sustainability of Regional Groundwater Quality in Response to Managed Aquifer Recharge - Zhilin Guo; Graham E. Fogg; Kewei Chen; Rich Pauloo; Chunmiao Zheng (Water Resources Research)
Abstract Growing demands on water supply worldwide have resulted in aquifer overdraft in many regions, especially in alluvial basins under intensive irrigation. This further leads to serious deterioration of groundwater quality. Managed aquifer recharge (MAR) has been shown to mitigate groundwater overdraft, but whether MAR can actually stabilize or reverse the ongoing declines in regional groundwater quality caused by non‐point sources has not been demonstrated. This study was intended to address the question by investigating impacts of different MAR strategies on regional groundwater quality. A geostatistical model was first used to characterize a heterogeneous alluvial aquifer system in a portion of the Tulare Lake Basin. Three‐dimensional numerical models were then employed to simulate groundwater flow and mass transport. Next, MAR strategies were applied in locations with different geological conditions or joint with different irrigation activities, and their performances were evaluated. Results demonstrate the potential of significant, long‐term benefits for regional groundwater quality by applying strategic, high‐intensity recharge operations on geologically favorable subregions. Siting MAR above the incised valley fill (IVF) deposit, a near‐surface paleochannel containing unusually coarse, high‐conductivity hydrofacies, leads to more extensive improvement in the groundwater quality in terms of salinity due to significant vertical flow and lateral outward flow from the IVF. Overall, decades would be required to alleviate groundwater quality concerns in the studied 189 km2 region. The simulations indicate that the deep concentrations remain below the secondary maximum contaminant level as the solute mass migrates downward with the prominent contribution from the attenuation via dispersion and matrix diffusion.